A new approach for measuring the muon anomalous magnetic moment and electric dipole moment. (30th May 2019) - Abe, M; Bae, S; Beer, G; Bunce, G; Choi, H; Choi, S; Chung, M; da Silva, W; Eidelman, S; Finger, M; Fukao, Y; Fukuyama, T; et al.
Abstract: This paper introduces a new approach to measure the muon magnetic moment anomaly a_μ = (g-2)/2 and the muon electric dipole moment (EDM) d_μ at the J-PARC muon facility. The goal of our experiment is to measure a_μ and d_μ using an independent method with a factor of 10 lower muon momentum, and a factor of 20 smaller diameter storage-ring solenoid compared with previous and ongoing muon g-2 experiments with unprecedented quality of the storage magnetic field. Additional significant differences from the present experimental method include a factor of 1000 smaller transverse emittance of the muon beam (reaccelerated thermal muon beam), its efficient vertical injection into the solenoid, and tracking each decay positron from muon decay to obtain its momentum vector. The precision goal for a_μ is a statistical uncertainty of 450 parts per billion (ppb), similar to the present experimental uncertainty, and a systematic uncertainty less than 70 ppb. The goal for EDM is a sensitivity of 1.5× 10^-21 e·cm .